2022
DOI: 10.1371/journal.pgen.1010309
|View full text |Cite
|
Sign up to set email alerts
|

RAD18 opposes transcription-associated genome instability through FANCD2 recruitment

Abstract: DNA replication is a vulnerable time for genome stability maintenance. Intrinsic stressors, as well as oncogenic stress, can challenge replication by fostering conflicts with transcription and stabilizing DNA:RNA hybrids. RAD18 is an E3 ubiquitin ligase for PCNA that is involved in coordinating DNA damage tolerance pathways to preserve genome stability during replication. In this study, we show that RAD18 deficient cells have higher levels of transcription-replication conflicts and accumulate DNA:RNA hybrids t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Figure 4A). In agreement with previous findings (Wells et al 2022), we found that RAD18 plays a role in FANCD2 recruitment upon MRS (Suppl. Figure 4B).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Figure 4A). In agreement with previous findings (Wells et al 2022), we found that RAD18 plays a role in FANCD2 recruitment upon MRS (Suppl. Figure 4B).…”
Section: Resultssupporting
confidence: 94%
“…These effects are partially dependent on the failure to recruit the Fanconi anaemia protein FANCD2 to R-loop-prone genomic sites (Wells et al 2022). Notably, in our context, FANCD2 localizes with R-loops after MRS, and this localization is more pronounced in cells lacking WRNIP1 and its UBZ domain.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We next investigated whether the PCNA ΔSL47 mutant affects genomic integrity in cells using various assays. Recent studies have shown that PCNA unloading, PCNA ubiquitination, and FEN1 are associated with DNA-RNA hybrids and R-loop regulation [39][40][41][42]. Since PCNA ΔSL47 showed a PCNA ubiquitination defect (Figs 3C, 3D and 4B-4D), similar to RAD18-deficient cells [40], we next assessed whether the PCNA ΔSL47 mutant affects cellular DNA-RNA hybrid levels.…”
Section: Pcna Ser46 and Leu47 Amino Acids Are Important For Genomic S...mentioning
confidence: 99%